2018
DOI: 10.1159/000490821
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: The New Mediator of Peritoneal Membrane Function

Abstract: Fibrosis and angiogenesis are the most common processes that result in progressive peritoneal tissue remodeling and, eventually, peritoneal membrane dysfunction. The role of exosomes, which contributes to intercellular communication, in these processes has been neglected. Various biomolecules, including DNA, mRNA, proteins, lipids, and particular certain miRNAs, can be transferred by exosomes to local, neighboring and distal cells. Upon stimulation by cytokines or other microenvironment stimuli, donor cells re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Exosomes are nano-sized extracellular vesicles originating from the endosomal pathway that exist in almost all body fluids and are promising source of biomarkers 28 . Exosomes carry a cargo of proteins, lipids and nucleic acids, that can participate in cell-to-cell signaling affecting nearby and distant cells 29 , playing a role in EMT and peritoneal fibrosis 30 , 31 , and in angiogenesis processes 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are nano-sized extracellular vesicles originating from the endosomal pathway that exist in almost all body fluids and are promising source of biomarkers 28 . Exosomes carry a cargo of proteins, lipids and nucleic acids, that can participate in cell-to-cell signaling affecting nearby and distant cells 29 , playing a role in EMT and peritoneal fibrosis 30 , 31 , and in angiogenesis processes 32 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have reported that peritoneal cells respond to the dialysis exposure by releasing various EVs, which can be found in PD effluent. 9 These PD effluent-derived EV proteomes showed alteration earlier than peritoneal equilibration test monitoring, suggesting the potential of EV proteins as biomarkers of peritoneal function alteration for patients undergoing PD. 10 Moreover, it has been reported that specific molecular cargo in EVs, such as aquaporin 1 and glycoprotein 96, can be used to evaluate the status of peritoneum.…”
Section: ■ Introductionmentioning
confidence: 90%
“…Since the specific molecular composition of EVs reflects physiological or pathological state of parent cells, EVs isolated from body fluids are increasingly recognized as promising biomarkers for disease progression . Previous studies have reported that peritoneal cells respond to the dialysis exposure by releasing various EVs, which can be found in PD effluent . These PD effluent-derived EV proteomes showed alteration earlier than peritoneal equilibration test monitoring, suggesting the potential of EV proteins as biomarkers of peritoneal function alteration for patients undergoing PD .…”
Section: Introductionmentioning
confidence: 99%
“…CXCL1 may be an important pro-angiogenic agent [ 67 ]. Catar et al showed that CXCL1 secreted by PMCs directly promotes human microvascular endothelial tube formation [ 67 ], and VEGF accelerates the PA process by participating in angiogenesis [ 68 , 69 ]. CXCL1 can also upregulate the expression of PAI-1 and promote fibrin deposition [ 3 ].…”
Section: The Mechanism Of Pmcs In Promoting Pasmentioning
confidence: 99%